ISLAMIC FINANCE IN ETHIOPIA: CURRENT STATUS, PROSPECTS AND CHALLENGES - Hailu, Suadiq Mehammed; Yatoo, Nissar Ahmad (International Journal of Islamic Banking and Finance Research, 2021)
Ethiopia is a country found in the horn of Africa and notable in the Muslim world as the destination of the two migration of the companions of Prophet Muhammad (PBUH). Ethiopia has a Muslim population expected to be around 50 million. Unfortunately, with this significant Muslim population, it accommodates Islamic finance in its conventional financial system lately. This study aims to investigate the current status, prospects, and challenges of Islamic finance in Ethiopia. For these reasons, different secondary data were collected and analyzed. The result of the study indicated that Islamic finance in Ethiopia is representing by three financial institutions such as Islamic banks, Islamic Insurance and Islamic microfinance. Islamic banking is providing through the Interest-free banking window and fully-fledged forms of interest-free banking. The interest-free banking window system is adopted by conventional banks, whereas Full-fledged Islamic Banks providing services using their own separate Sharia-compliant financial system. The result also indicated that high public demand, adequate capital for the establishment, availability of substantial customers, easy deposit mobilization and profitability are the foremost opportunities for Islamic finance in Ethiopia. Whereas, negative perception about Islamic finance, legal framework challenges such as restriction of investment and double taxation, and lack of skilled human resources are the main potential hindrances for the sector. JEL Classification Codes: F65, G21, G22.